Diagnostic Accuracy of Lung Ultrasound in Diagnosis of Pneumonia in Children using Chest X-RAY as Gold Standard - Nosheen Sadiq; Iftikhar, Ammara; tahir, Myra; Mahmood, Rashid; Awan, Aamir Aslam; Uzair, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the diagnostic accuracy of lung ultrasound (LUS) in the diagnosis of pneumonia in children using chest x-ray as the gold standard.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Radiology, Combined Military Hospital, Sialkot Pakistan, from Feb to Aug 2021Methodology: All patients underwent clinical examination, chest radiograph (anterior-posterior view), lung ultrasound and blood sample analysis in the first 24 hours after admission. A pre-specified hospital radiologist carried out a lung ultrasound. The examination was performed with the patient sitting upright or supine. The presence of pneumonia on x-ray and USG were recorded. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of lung ultrasound in the diagnosis of pneumonia by taking chest x-ray as the gold standard was calculated in all the study participants.Results: In this study, 262 patients with clinical features of pneumonia were enrolled. The mean age of the study participants was 3.27±2.344 years. Sensitivity (Se), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV), accuracy and frequency of lung ultrasonography (US) vs chest radiography (CR) in diagnosing pneumonia was 95.28%, 87.5%, 99.59%, 36.84%, 95.04% and 96.95% respectively.Conclusion: Lung ultrasound emerged as a sensitive diagnostic tool to diagnose pneumonia in children. Sensitivity, specificity, positive predictive value, and negative predictive value all favoured the use of this modality to diagnose pneumonia in paediatric patients.